Albanian university students' knowledge, attitudes, and practices regarding COVID-19 infection and vaccine: A cross-sectional study - Merkuri, Lumturi; Puca, Edmond; Kamberi, Fatjona; Alimehmeti, Ilir; Qorri, Erda; Borshi, Xhejni (The Journal of Infection in Developing Countries, 2023)
Introduction: COVID-19 pandemic remains a public health concern worldwide. Given that, students represent a subgroup of the population with an impact on the pandemic. Aim: The aim of this study is to evaluate the knowledge, attitudes, and practices of Albanian students about COVID-19, and to provide a database to plan and implement preventive evidence-based interventions. Methodology: An online survey was conducted among Albanian university students during April-May 2022, to collect information on their knowledge, attitudes, and practices related to COVID-19, through a structured questionnaire. Results: A total of 906 students, 72.8% females, were included in it. 93.4% of participants knew the ways of transmission of COVID-19; 92.5% had information about preventive measures, but only 30% knew about quarantine and 37.0% knew vaccination as a preventive measure. Regarding attitudes, 54.8% of participants believed that COVID-19 infection is very dangerous. 46.5% have a negative attitude toward covid vaccines. Almost all respondents (93.7%) apply regular hand washing as a preventive measure; 82.8% cover their mouth when coughing or sneezing; but only 28.2% always use a mask indoors. Conclusions: Albanian university students had good knowledge, positive attitudes, and appropriate preventive practices against COVID-19, but the study found that some limitations in terms of information and misconceptions still exist. Raising awareness and providing adequate information, education, and more effective communication programs will have a positive impact on increasing knowledge, improving attitudes, and supporting the required student behavior change.